Household Expenditure Analysis of Hybrid Coconut Farmers in Tempuling District Indragiri Hilir Regency Riau Province - Annikmah, Asylla Syifa; Vaulina, Sisca (Tarjih : Agribusiness Development Journal, 2024)
The decline in coconut prices negatively affects farmers' income, thus impacting overall household expenditures. This study aims to analyze (1) the characteristics of hybrid coconut farmers, (2) the structure of household income of hybrid coconut farmers, (3) household expenditures of hybrid coconut farmers, and (4) the factors influencing household expenditures of hybrid coconut farmers. The research used a survey method with purposive sampling, resulting in a sample size of 53 farmers. Multiple linear Regression was the primary analytical tool. The results showed that: (1) Farmers had an average age of 44 years, 9.6 years of education, 21 years of farming experience, four family members, and an average land area of 3.31 hectares. (2) Household income was primarily derived from hybrid coconut farming (60.53%). (3) The most significant household expenditure was on non-food items (53.46%), including housing, education, health, clothing, and recreation. (4) Significant factors influencing household expenditures included household income (X1), number of family members (X2), and assets (X6). Conversely, the farmer's education level (X3), wife's education (X4), and savings (X5) did not significantly affect the household expenditures of hybrid coconut farmers. This study provides novel insights by revealing the role of assets as a buffer factor that can enhance household consumption through asset sales, which has not been widely explored in previous research on hybrid coconut farmers.